TANGGUNG JAWAB GENERASI MUDA TERHADAP DEMOKRASI BAGI MASA DEPAN NEGARA - Zahra, Fathimatuz (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Pancasila values must be instilled in the younger generation from an early age because it is very important to know how to be a good, responsible generation, always apply the values of divinity, humanity, unity and populist values, because it is based on current life where the millennial generation has begun to forget the Pancasila life guidelines, and the shift in Pancasila values in the current environment of human life has changed with globalization. The methodology used is a qualitative method where the approach is carried out through a observation study. This writing is based on the fading of the values of Pancasila ideology in the life of generation millenial, the cause of the fading of Pancasila values in life, and the consequences of the fading of Pancasila values in life. The purpose of this paper is for the public to know that the application of Pancasila values in life is very important, especially in facing the era of globalization. more individuals than social attitudes in their environment. That is why it is very important to apply Pancasila values for the next generation of the nation who Also known as the millennial generation. The purpose of writing this journal is to develop and maintain Pancasila values, especially for the millennial generation.